Real-Time Polymerase Chain Reaction for the Rapid Detection of Group B Streptococcal Colonization in Neonates - Natarajan, Girija (2006)
BACKGROUND: Group B streptococcal (GBS) infection remains a leading cause of neonatal sepsis. Currently, the management guidelines of neonates born to women with unknown GBS status at delivery are unclear. In this cohort, who undergo at least a 48-hour observation, a rapid method of detection of GBS colonization would allow targeted evaluation and treatment, as well as prevent delayed discharge. OBJECTIVE: The goal of this research was to evaluate the validity of rapid fluorescent real-time polymerase chain reaction in comparison with standard culture to detect GBS colonization in infants born to women whose GBS status is unknown at delivery. DESIGN/METHODS: Neonates at > 32 weeks’ gestation born to women whose GBS status was unknown at delivery were included. Samples were obtained from the ear, nose, rectum, and gastric aspirate for immediate culture and real-time polymerase chain reaction after DNA extraction using the LightCycler. Melting point curves were generated, and confirmatory agar gel electrophoresis was performed. RESULTS: The study population (n = 94) had a mean ± SD gestational age of 38 ± 2 weeks and birth weight of 3002 ± 548 g. The rates of GBS colonization by culture were 17% and 51% by real-time polymerase chain reaction. The 4 surface sites had comparable rates of GBS. The overall sensitivities, specificities, and positive and negative predictive values of real-time polymerase chain reaction were: 90%, 80.3%, 28%, and 98.9%. CONCLUSIONS: Real-time polymerase chain reaction resulted in a threefold higher rate of detection of GBS colonization and had an excellent negative predictive value in a cohort of neonates with unknown maternal GBS status at delivery. Thus, real-time polymerase chain reaction would be a useful clinical tool in the management of those infants potentially at risk for invasive GBS infection and would allow earlier discharge for those found to be not at risk.